Capacity Building for the Community of Air Anyir Village through Training on Processed Fish-Based Food Products - Rifky Amri Amrullah (Prospect: Jurnal Pemberdayaan Masyarakat, 2023)
This journal focuses on the capacity building efforts targeted towards the community of Air Anyir Village with a specific emphasis on enhancing their skills and knowledge in the production of processed fish-based food products. Recognizing the importance of economic empowerment and sustainable livelihoods, this study aims to investigate the impact of training programs on the community's capacity to develop and market value-added fish products. The findings of this study will provide valuable insights into the effectiveness of capacity-building initiatives for rural communities in developing processed fish-based food products. The research outcomes will be crucial in shaping future interventions and policies aimed at promoting sustainable livelihoods, community empowerment, and economic growth in similar contexts.